Sewn boats in the Qatar Museums collection, Doha: baggāras and kettuvallams as records of a western Indian Ocean technological tradition. (1st September 2020) - Cooper, John P.; Ghidoni, Alessandro; Zazzaro, Chiara; Ombrato, Luigi
Abstract: Vernacular sewn boats from southern Iran and Kerala, India, in the collection of Qatar Museums are documented and their construction described. The Iranian baggāra s are unique preservations of sewn boats from the Arabian‐Persian Gulf, notable for their previously undocumented keel‐garboard sewing technique and extensive use of bitumen coatings. Comparison between individual boats enables conclusions to be drawn about the builders' conception, as well as variation within the type. The Keralite kettuvallam s represent an ongoing vernacular tradition that is nevertheless poorly documented or preserved in museum contexts. Construction drawings, naval‐lines drawings, and 3D photogrammetry models are provided for all vessels.